Monitoring and Bio rationale Management of Tuta absoluta [Lepidoptera: Gelechiidae] in Tomato in Western Nepal (Nepalese Horticulture, 2025)
Tuta absoluta (Meyrick), the tomato leaf miner, is a major pest of tomato in Nepal, and can cause an 80–100% reduction in yield if left untreated. Monitoring of the adult moth population and a field experiment were conducted in Surkhet District, Nepal, with eight treatments replicated three times in a RCB design. The tested treatments included (i)Bacillus thuringiensis var. kurstaki (Bt.k) @2 g/L of water, (ii) Nimbicidine (Azadirachtin 300 ppm) @4 ml/L of water (iii) Neem 1500 (Azadirachtin 0.15 EC) @4 ml/L of water, (iv) B. bassiana (2.0% A.S.) @4 ml/L of water, (v) Bacculo virus, SC, >2x1013 (TutaVir) @2ml/10L of water, (vi) Alternate spray of Bt.k and Neem 1500 and (vii) Chlorantraniliprole 18.5% SC (standard check), and (viii) Water spray (control). Observations were made in six-day intervals, in which data on leaf damage, bud damage percentage, percent fruit damage, as well as average number of larvae, bore hole, and yield attributes were recorded. The monitoring results revealed the average population of moths above Economic Threshold Level (ETL). The percentage fruit damage was lowest in the Chlorantraniliprole 18.5% SC (1.48%) followed by alternate spray of Bt.k and Neem 1500 (1.81%) while the marketable yield was at par in both treatments. The B:C ratio showed that alternate spray of Bt.k and Neem 1500 and Chlorantraniliprole 18.5% SC were the superior as compared to others.  This study concludes that the alternate spray of Bt.k and Neem 1500 is the most effective biorational pesticide for the management of T. absoluta in field conditions.